Eosinophilic leukaemia with trisomy 8 and double gammopathy. Issue 7 (July 1993) - Ribeiro, I; Carvalho, I R; Fontes, M; Lima, F; Matos, R; Anderson, B A; Uva, L S
Abstract : Prolonged eosinophilia of unknown cause has generally been described as the hypereosinophilic syndrome, and is characterised by peripheral blood and bone marrow infiltration and frequent multisystem disease. The nature of this disorder has been questioned, and the clinical features are quite variable, suggesting its heterogeneity and probable neoplastic aetiology. A patient with severe eosinophilia, karyotype abnormalities, serum gammopathy and massive organ disease is reported. The clinical course was aggressive despite cytoreduction of eosinophils and terminated in multisystem failure. These findings are consistent with a diagnosis of eosinophilic leukaemia, and it is suggested that chromosome and cell culture studies might be useful in the early diagnosis of this controversial entity.